Parainfluenza Virus Types 1–3 Infections Among Children and Adults Hospitalized With Community-acquired Pneumonia. (18th July 2020) - Howard, Leigh M; Edwards, Kathryn M; Zhu, Yuwei; Williams, Derek J; Self, Wesley H; Jain, Seema; Ampofo, Krow; Pavia, Andrew T; Arnold, Sandra R; McCullers, Jonathan A; Anderson, Evan J; Wunderink, Richard G; et al.
Abstract: Background: Parainfluenza virus (PIV) is a leading cause of lower respiratory tract infections. Although there are several distinct PIV serotypes, few studies have compared the clinical characteristics and severity of infection among the individual PIV serotypes and between PIV and other pathogens in patients with community-acquired pneumonia. Methods: We conducted active population-based surveillance for radiographically confirmed community-acquired pneumonia hospitalizations among children and adults in 8 US hospitals with systematic collection of clinical data and respiratory, blood, and serological specimens for pathogen detection. We compared clinical features of PIV-associated pneumonia among individual serotypes 1, 2, and 3 and among all PIV infections with other viral, atypical, and bacterial pneumonias. We also compared in-hospital disease severity among groups employing an ordinal scale (mild, moderate, severe) using multivariable proportional odds regression. Results: PIV was more commonly detected in children (155/2354; 6.6%) than in adults (66/2297; 2.9%) ( P < .001). Other pathogens were commonly co-detected among PIV cases (110/221; 50%). Clinical features of PIV-1, PIV-2, and PIV-3 infections were similar to one another in both children and adults with pneumonia. In multivariable analysis, children with PIV-associated pneumonia exhibited similar severity to children with other nonbacterial pneumonia, whereas children with bacterial pneumonia exhibited increased severity (odds ratio, 8.42; 95% confidence interval, 1.88–37.80). In adults, PIV-associated pneumonia exhibited similar severity to other pneumonia pathogens. Conclusions: Clinical features did not distinguish among infection with individual PIV serotypes in patients hospitalized with community-acquired pneumonia. However, in children, PIV pneumonia was less severe than bacterial pneumonia. Abstract : Clinical features did not reliably distinguish pneumonia with different parainfluenza virus (PIV) serotypes. Among children, PIV pneumonia was less severe than bacterial pneumonia, but in adults the severity of PIV pneumonia did not significantly differ from other pathogens.